Double Bordering of the Nicosia Historic Centre: Contested Heritage, Divisions, and Attachments of the Walled City - Pasamitros, Nikolaos; Krikoni, Veroniki (HAPSc Policy Briefs Series, 2024)
Nicosia is a place of double bordering where the Venetian wall surrounds the old city and simultaneously the Green Line cuts through its historical nucleus and separates it into two distinct administrative parts, a north and a south one. Authorities in the Greek Cypriot (GC) and Turkish Cypriot (TC) communities exercise policies that use the division of the city in order to construct and promote ethnocentric narratives. Similarly, heritage management and use are driven by ethnocentric political aims, based on a national heritage perception framework that fortifies and regulates national identity. Ethnocentric heritage discourse is challenged by a universalist framework that tries to foster reconciliation through bicommunal projects. Although this framework produces significant collaborative heritage projects, it is criticised for promoting externally imposed universalism. Alternatively, recent heritage theory and local practice in the historic centre of Nicosia stress the significance of inclusive approaches to heritage that would further encourage the involvement of local heritage communities, increase the sense of heritage ownership, involve underrepresented communities, and open a dialogue on dissonant heritage.